Atmospheric Paleoart: A Case Study of the Murals in the Paleozoological Museum of China - Qi Wang; Yuan Wang; Adam S. Smith (Geoconservation Research)
Expansive works of paleoart in natural history museums have the power to set the atmosphere in a gallery space. In this sense, the artwork can be described as atmospheric. Atmospheric paleoart is usually thematically associated with the surrounding objects on display, where it can enhance the exhibition narrative and become an independent display object itself. Atmospheric paleoart also plays a significant role in the public understanding of paleontology. The Paleozoological Museum of China in Beijing contains three large murals as part of its key exhibition narrative. These expansive paintings were installed for the public opening of the museum in 1994, but they are poorly documented. Each mural showcases one of the three ‘ages of life’– the Paleozoic, Mesozoic, and Cenozoic – as represented predominantly by prehistoric biotas from China. This paper provides a record of these important murals, focusing on their scientific and social value, while exploring perspectives on the development of paleoart in China.